Motives as desirable result - Vasiliauskas , A. (Psichologija, 1969)
The problem of systematic description of the motives of personality’s conscious activity is investigated. “Systematic” we call such a description of the motives that is based on particular concept of psychological phenomena of the motives, without using various correlative concepts. Psychological phenomena of the motive of personality's conscious activity consist of the desirable result (outcome) of the activity. From this point of view the supposed result foreseen by the subject as undesirable cannot be estimated as motive of his conscious activity. The supposed results which evoke fear, shame, disappointment and other negative experiences of the subject are not the motives. This concept enables us to describe various cases of human activity in term of aspiration for the desirable results. The whole human activity in this way can be classified in to some general or formal cases (case of interest, duty, compulsion, etc.) which are characterised by the emotional state of the subject and by the relation between the motive and counter-motive. Such characteristics could be used in analysis and classification of the behavioural data of the personality to reveal the motives of its activity.
Keywords: motives; motivation